Factors Associated with the Incidence of Dermatitis at the Nagaswidak Community Health Center in Seberang Ulu II District, Palembang City, in 2025 - Nuril Fazriah (Journal of Innovative and Creativity, 2026)
Dermatitis remains a significant public health concern in resource-limited settings. This study examined associations between knowledge, personal hygiene practices, water source quality, and dermatitis incidence. A cross-sectional analytical design involved 130 respondents stratified from 250 dermatitis cases at Nagaswidak Community Health Center, Palembang City, from July to August 2025. Data were collected using structured questionnaires with 30 items measuring demographic characteristics, dermatitis knowledge (11 items), personal hygiene practices (13 items), and water source characteristics (6 items). Dermatitis diagnosis was confirmed through clinical examination and medical records review. Analysis employed chi-square testing at α = 0.05 significance level using IBM SPSS Statistics version 26. Results demonstrated statistically significant associations between all three variables and dermatitis incidence. Individuals with inadequate knowledge exhibited 1.920 times greater dermatitis risk compared to those with adequate knowledge (p = 0.000). Poor personal hygiene demonstrated 1.845 times elevated risk relative to good hygiene (p = 0.000). Poor water source quality showed 1.733 times higher risk than adequate water sources (p = 0.000). This investigation concluded that knowledge deficits, inadequate personal hygiene, and poor water source quality constitute modifiable risk factors requiring integrated public health interventions addressing individual behavior modification, hygiene practice standardization, and environmental sanitation infrastructure improvement.